A Study of the Clinical Utilization of Cryoprecipitate at King Abdulaziz University Hospital - Galila F. Zaher; Soheir S. Adam (Journal of King Abdulaziz University: Medical Sciences, 2023)
Many guidelines for cryoprecipitate utilization have been published, yet there is little evidence that these guidelines are being followed. A retrospective study was conducted to assess the appropriateness of cryoprecipitate utilization, based on pre-implemented guidelines over a four years period at King Abdulaziz University Hospital. Eighty-five patients who received 705 units cryoprecipitate were included. Transfusion was assessed according to the predetermined appropriateness criteria. Cryoprecipitate was used inappropriately in 48.1% of cases. Transfusion was for the following appropriate indications: hypofibrinogenemia (n = 20), factor deficiency (n = 8), management of massive transfusion (n = 8), postpartum bleed and for correction of uremic bleeding. Most appropriate cryoprecipitate usage occurred when there was secondary hypofibrinogenemia with active bleeding (19.9%). Cryoprecipitate was misused in almost half of the patients in the study. The most common inappropriate medical indication was to correct uremic bleed, while the most common surgical indication was for correction of surgical bleeding in the absence of a specific factor deficiency (22.5%). Internal audit could help identify the pattern of misuse. Education among the medical community can help improve cryoprecipitate utilization.